Continuity and Change: Virtual Communication Among High School Students in Medan After Covid-19 Pandemic - Rudianto Rudianto; Akhyar Anshori; Yan Hendra (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The COVID-19 pandemic accelerated the integration of digital communication into students' academic and social lives, fostering hybrid communication patterns. However, post-pandemic research comprehensively examining the continuity of these patterns through integrated quantitative and qualitative approaches remains limited, particularly at the senior high school level. This gap warrants further investigation to understand how face-to-face and virtual interactions adapt and complement one another in the post-pandemic educational context. Objective: This study aims to analyze the communication behavior of high school students in Medan after the COVID-19 pandemic, focusing on the continuity of teaching and learning activities, interactions with peers, and communication with family. Methods: An explanatory sequential mixed-methods design was applied. Quantitative data were collected through structured questionnaires from 1,500 students across 30 high schools, followed by qualitative data from 30 semi-structured interviews. Quantitative analysis employed descriptive statistics and cross-tabulation, while qualitative data were analyzed using thematic coding and categorization. Results: Students continue practicing hybrid communication combining face-to-face and virtual modes, with 78% reporting daily virtual communication for academic purposes. Virtual platforms enhance flexibility in information exchange, learning access, and schedule coordination. Challenges persist, however, including limited digital literacy, restricted online interaction time, and unstable internet connectivity, creating participation disparities. Conclusion: The study underscores the importance of addressing the digital divide and improving infrastructure to support effective virtual communication. By identifying both the benefits and obstacles of virtual communication, this research contributes to developing strategies that enhance the educational experience for high school students in Medan in the post-pandemic era.